2022
DOI: 10.3389/fpubh.2022.849059
|View full text |Cite
|
Sign up to set email alerts
|

Operational Characteristics of Women Street Food Vendors in Rural South Africa

Abstract: ObjectiveTo characterize the operations of the street food enterprise in the Vhembe district, focusing on business profile, sold foods, inputs, pricing, record-keeping practices and total running cost.MethodsA descriptive cross-sectional face-to-face study of 511 vendors was done using a structured researcher-administered questionnaire comprising demographic and operational characteristics. Convenience sampling was used to choose the vending sites. Chi-square tests were conducted between four categorical varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In the current study, we observed poor institutional support for street food vendors along the value chain of street food. In previous publication [26,27], we highlight that street food vendors have agreements amongst those selling vegetables whereby they take inputs on credits to pay after the sale, something absent from the formal retailer as street food vendors are not allowed to make any credits from the formal institutions. The study highlighted the support of the informal sectors such as transport because most street food vendors used public transport to fare the input to their stalls [40].…”
Section: Financial Institutionsmentioning
confidence: 98%
See 3 more Smart Citations
“…In the current study, we observed poor institutional support for street food vendors along the value chain of street food. In previous publication [26,27], we highlight that street food vendors have agreements amongst those selling vegetables whereby they take inputs on credits to pay after the sale, something absent from the formal retailer as street food vendors are not allowed to make any credits from the formal institutions. The study highlighted the support of the informal sectors such as transport because most street food vendors used public transport to fare the input to their stalls [40].…”
Section: Financial Institutionsmentioning
confidence: 98%
“…Culled layers, and beef offal gives street vendors a competitive advantage since these products are a by-product being sold from major poultry and beef processing facilities [27]. The same applies to green leafy vegetables which are purchased form Bakkies or produced by street vendors in their back yards.…”
Section: Purchasingmentioning
confidence: 99%
See 2 more Smart Citations
“…In Senegal as in many LMIC, food safety remains one of the major concerns with multiple challenges. Street foods have developed strongly over the past thirty years [11,15,[23][24][25]. This phenomenon is linked to the combined effect of changing eating habits [19], rural exodus, population growth in cities and also due to the high annual production of horticultural products [21].…”
Section: Introductionmentioning
confidence: 99%